MENINGKATKAN KUALITAS PELAYANAN BISNIS MAKANAN PEMPEK DI KOTA PALEMBANG - Muhammad Yusuf (Politeknik Negeri Sriwijaya, 2015)
Pempek is a typical food Palembang and very popular. The much number of business competitions in the field of pempek requires the businesses need to improve the quality of service to become win the competition. This study aims to determine the effect of the dimensions of service quality on customer satisfaction pempek store in Palembang. This research was conducted at the store Pempek